Dithering Analysis in an Orthogonal Frequency Division Multiplexing-Radio over Fiber Link - Fakhriy Hario P; Adhi Susanto; I Wayan Mustika; Sevia M Idrus; Sholeh Hadi P (Institute of Advanced Engineering and Science, 2016)
Nonlinearity is one major problem broadband communication faced on utilizing the high capacity of optical fibers. That is due to scattering phenomenon, which results in the deviations of wavelengths and energies. The dithering method is applied in the attempt to reduce those scatterings. In this paper, we propose the performance of a dithering technique based new system OFDM-RoF using two modulator scheme and coherent detection to alleviate the characteristics nonlinearity applied on the system. The dithering technique inputs signal externally to the signal processing systems to eliminate the effects of nonlinearity. Here, we report the performance of a dithering technique based on the OFDM-RoF, the results our experiment showed that the applied dithering with 16 QAM modulation can make the system more reliable and increases the power level 1.55% with 193.1 THz, 2% with 100 THz and 1.99% 200 THz, the best condition are with fd < fc. However, all condition close proximity in the parameters OLP (optical launch power), BER and SER measurement. The result demonstrated a high efficiency and good power in which the OLP operated 6.396 dBm / 4.361 E-3 W fd 200 THz, 3.578 dBm / 2.279 E-3 W fd 193.1 THz and 6.420 dBm / 4.3384 E-3 W 100 THz. The best BER value is achieved at 0.33 and SER 0.78 at 5 km fd 100 THz, 0.33 and 0.768 for 10 km fd 193.1 THz, 0.478 and 0.92 for 50 km fd 193.1 THz.